Perinatal Factors Associated with Cardiovascular Disease Risk among Preschool-Age Children in the United States: An Analysis of 1999-2008 NHANES Data - Sarah E. Messiah; Kristopher L. Arheart; Steven E. Lipshultz; Emmalee S. Bandstra; Tracie L. Miller (Hindawi Limited, 2012)
We examined the relationships between selected perinatal and early infancy factors (maternal smoking during pregnancy, infant low birthweight, breastfeeding, and early introduction of solid foods [<6 months of age] and increased BMI [≥85th, ≥95th percentiles for age, sex]), waist circumference (WC), C-reactive protein (CRP), triglycerides, total cholesterol, low-density lipoprotein (LDL) cholesterol, non-high-density lipoprotein (HDL) cholesterol, and decreased HDL cholesterol during early childhood. The population-based sample included 3,644 3-to-6-year-old Non-Hispanic White (NHW), Hispanic, and Non-Hispanic Black (NHB) children who participated in the 1999-2008 National Health and Nutrition Examination Surveys. Analysis showed that breastfeeding was significantly protective against early childhood obesity (OR 0.43, 95% CI, 0.27-0.69) and the highest quintile for WC (OR 0.58, 95% CI, 0.37-0.32) among NHW, and against the highest quintile of non-HDL cholesterol among NHB (OR 0.56, 95% CI, 0.32-0.98). Additionally, NHW children were significantly more likely to be obese (OR 2.22, 95% CI 1.30-3.78) and have higher CRP levels (OR 1.63, 95% CI, 1.05-2.51) if their mothers smoked during pregnancy. These results support the observation that breastfeeding may be protective against early childhood obesity while maternal smoking during pregnancy is a risk factor for obesity and increased CRP levels among NHW young children.